2017
DOI: 10.3144/expresspolymlett.2017.92
|View full text |Cite
|
Sign up to set email alerts
|

The improvement of mechanical and thermal properties of polyamide 12 3D printed parts by fused deposition modelling

Abstract: Abstract. This paper addresses the utilisation of fused deposition modelling (FDM) technology using polyamide 12, incorporated with bioceramic fillers (i.e. zirconia and hydroxyapatite) as a candidate for biomedical applications. The entire production process of printed PA12 is described, starting with compounding, filament wire fabrication and finally, FDM printing. The potential to process PA12 using this technique and mechanical, thermal and morphological properties were also examined. Commonly, a reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 51 publications
3
36
0
Order By: Relevance
“…After that, it was followed by a second yielding, including the second hardening stage and the second cold‐draw stage (or third yielding), until the samples fractured during the third hardening finally. Similar phenomenon has been observed in other polymers, such as PE, PA6, and PA12 . In our study, the mechanism of this interesting phenomenon might be related with the microphase structure of copolymers and the chain alignment during the tension process.…”
Section: Resultssupporting
confidence: 88%
“…After that, it was followed by a second yielding, including the second hardening stage and the second cold‐draw stage (or third yielding), until the samples fractured during the third hardening finally. Similar phenomenon has been observed in other polymers, such as PE, PA6, and PA12 . In our study, the mechanism of this interesting phenomenon might be related with the microphase structure of copolymers and the chain alignment during the tension process.…”
Section: Resultssupporting
confidence: 88%
“…Among the different technologies applicable for graphene-polymer products fabrication, the additive manufacturing (e.g., 3D printing) is the most promising since it is generally applicable to different types of polymers and is a versatile and low-cost technology. The development of new conductive polymer nanocomposite materials for 3D printing is highly desirable to achieve better printability, mechanical properties, electrical and thermal conductivity [20][21][22][23][24][25][26][27][28]. Three methods most frequently used to obtain a dispersion of nanofillers into a polymer matrix in order to produce a filament are: solution mixing, melt blending, and in situ polymerization [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…The most common type of material extrusion additive manufacturing (MEAM) is a low-cost process in which a filament is softened, and the soft material is pushed through an orifice, The extrudate is then selectively deposited layer-by-layer to shape a threedimensional object [1]. It has been demonstrated that it is possible to use MEAM for the production of complex-shaped parts not only made out of thermoplastics [1][2][3][4][5][6][7][8][9][10][11][12][13][14] and low melting point metals alloys, but also high-melting-point metallic alloys [1,[15][16][17][18][19], ceramics [20][21][22][23][24][25][26][27][28][29][30][31][32][33], and cermets [34]. In order to obtain metallic, ceramic and cermet parts, highly-filled filaments are used as the feedstock material; the shaped part is then subjected to a process of binder removal and sintering to densify the parts [1], similar to the procedure common in powder injection moulding [2].…”
Section: Introductionmentioning
confidence: 99%